Open-source 3D printable forearm crutch - Maryam Mottaghi; Morgan Woods; Laura Danier; Anita So; Jacob M. Reeves; Joshua M. Pearce (PLoS ONE, 2025)
Although there has been considerable progress in distributed manufacturing of open-source designs for mobility aids, there is a notable lack of affordable, open-source crutches. Crutches are a vital tool for many individuals with mobility impairments, yet the high costs limit accessibility. Even more, they are in short supply in regions undergoing conflict. The goal of this study is to address this need by leveraging the principles of free and open-source hardware and the capabilities of digital distributed manufacturing to create a low-cost, functional crutch that can be easily produced and customized locally using inexpensive desktop 3D printers. All the design files are open-source, and the design process incorporated load-bearing tests using a hydraulic actuator under static loading conditions to meet the ISO 11334-1:2007 standard for walking aids. The open-source forearm crutch developed in this study not only surpasses the requirements of the ISO method for load capacity (1,516.3 ±  169.9 N, which is 51.6% percent above needs), weighs a fraction of comparable commercial systems (0.612 kg or 27% of proprietary devices), and is customizable, but also offers a highly cost-effective solution; costing CAD $36 in material, which is less than all equivalent crutches on the open market. If recycled plastic is used, the material cost of the crutch could be further reduced to under CAD $13, making it much more accessible.